An overview of assessment of competences based on publications in journals - Souza, Mariane Cásseres (2020)
Competences assessment transcends disciplinary areas and its research has increased worldwide. However, research in competence assessment in the engineering universe is something relatively new, concerning other disciplinary areas such as medicine and education. Understanding the state of art in areas where studies on competence assessment are more developed is an important step for transferring that knowledge to Engineering. This article aims to analyze the competences assessment state of art and to understand the actors involved in assessment methods (who is the assessor and who is being assessed), when and how the assessment process occurs, in medicine context, education, and engineering areas. The chosen approach was to carry out a literature review study based on a search using the Elsevier Scopus indexing service, in the timeframe 2000 to 2019. Using the search-terms "competences evaluation", "competencies evaluation", "competencies assessment" or "competences assessment", applied to title, abstract and keywords, was possible to identify 1,984 periodical documents, which 1,563 documents were of interest to the study, and related to Medicine, Education or Engineering areas. As a selection factor, the ten (10) most cited articles in each area were analyzed. Based on the study, the authors concluded the methods of assessing competences in medicine and education field may be used to support the Engineering area to develop reliable and valid methods for assessing competences. Besides, it was possible to identify that engineering competence assessment methods presented a focused computers simulators use. However, for medicine and education, the methods focus was evidenced in Objective Structured Clinical Examinations (OSCEs), based on scenarios.